Corticosteroids Versus Pentoxifylline for Severe Alcoholic Hepatitis: A Sequential Analysis of Randomized Controlled Trials. Issue 10 (November 2016) - Njei, Basile; Do, Albert; McCarty, Thomas R.; Fortune, Brett E.
Abstract : Introduction: Despite the significant morbidity and mortality associated with alcoholic hepatitis, a consensus or generally accepted therapeutic strategy has not yet been reached. The purpose of this analysis was to evaluate the effects of corticosteroids and pentoxifylline on short-term mortality, incidence of hepatorenal syndrome, and sepsis in patients with severe alcoholic hepatitis. Materials and Methods: We conducted a comprehensive search of the Cochrane library, PUBMED, Scopus, EMBASE, and published proceedings from major hepatology and gastrointestinal meetings from January 1970 to June 2015. All relevant articles irrespective of language, year of publication, type of publication, or publication status were included. Two independent reviewers extracted data and scored publications; a third investigator adjudicated discrepancies. The κ scores were measured to assess the agreement between the 2 initial reviewers. The review and meta-analyses were performed following the recommendations of The Cochrane Collaboration. Conventional meta-analysis and Trial sequential analysis were performed. GRADEpro version 3.6 was used to appraise the quality of epidemiologic evidence. Results: A total of 14 studies satisfied inclusion criteria comparing corticosteroids, pentoxifylline, or placebo. Compared with placebo, corticosteroids reduced 28-day mortality (RR=0.53; 95% CI, 0.33-0.84; P =0.006). There was no statistically significant difference in short-term mortality between pentoxifylline and placebo (RR=0.74; 95% CI, 0.46-1.18; P =0.21). Neither corticosteroids nor pentoxifylline impacted the incidence of hepatorenal syndrome or sepsis. Trial sequential analysis confirmed the results of our conventional meta-analysis. Conclusions and Relevance: Corticosteroids demonstrated a decrease in 28-day mortality in patients with severe alcoholic hepatitis. The evidence from this study is insufficient to support any recommendations regarding the mortality benefit of pentoxifylline in severe alcoholic hepatitis. Abstract : Supplemental Digital Content is available in the text.